Produção de surfactina por Bacillus subtilis UFPEDA 438 utilizando melaço de cana como substrato - Rocha, Patrícia Maria (2017)
The biosurfactants are drawing attention of both academy and industry by showing advantages mainly when compared to the chemical surfactants since they can be produced using renewable resources by fermentation. Among the different classes of biosurfactants lipopeptides outstand by their antibiotic activities, mainly the biosurfactant known as surfactin. Due to its properties it has been used in many fields such as bioremediation, biology, medicine and so on. However, as the others biosurfactants the production cost still is the bottleneck. Then the use of lower cost substrate can be one strategy in order to reduce the production costs. In this study the surfactin was produced by Bacillus subtilis UFPEDA 438 using sugarcane molasse as substrate in order to reduce costs. The microoganism was cultivated in rotatory shaker using a medium containing 4% surgacane molasse. The influence of temperature, agitation as well as the aeration ratio in the surfactin production was investigated. The samples were taken during cultivation until 72 h in order to record the substrate and cells concentration, the concentration of surfactin produced and medium pH. The results showed that for the best cultivation condition (200 rpm, 36 ºC and 0.4 aeration ratio) the concentration of surfactin was 199.45 ± 0.13 mg/L reached after 24 h, the substrate to product yield (YP/S) was 0.022 g/g and product productivity (PP) was 8.19 mg/L.h after 24 h. The pH was stable during all cultivation experiments ranging from 6.2 to 6.7 also a large residual content of substrate was observed. The Critical Micellar Concentration (CMC) of the produced biosurfactant at the best cultivation condition was 20.73 mg/L, thus showing good efficiency as surface agent. Also, it showed an emulsification index after 24 h (E24) of 62.0% for kerosene and capacity of forming emulsion of high stability reaching values of approximately 1.5U.